Studies of intrinsic resolution to low energy electron and muon neutrino events with neutrino telescopes - Hofestädt, J.; James, Clancy (2015)
Existing large-volume neutrino telescopes such as ANTARES and IceCube, as well as the future KM3NeT/ARCA, investigate neutrinos at characteristic particle energies of 10 TeV, whereas KM3NeT/ORCA and PINGU will operate around 10 GeV to determine the neutrino mass hierarchy by measuring the energy and direction of atmospheric neutrinos. In this energy regime, intrinsic fluctuations in particle behaviour become important. These intrinsic fluctuations are investigated to answer two basic questions. Firstly: How do intrinsic fluctuations limit the reconstruction accuracy of an perfect detector, i.e. if every single photon is detected? While this requires making some basic assumptions about the methods used in the reconstruction, the answer to this question will indicate the optimum that could be achieved by any detector. Secondly: Given that only a finite number of photons will be detected, what is the best possible reconstruction accuracy in the case of a ideal use of the information carried by these photons? For this study the baseline design of the KM3NeT/ORCA detector is used. This investigation separately considers muon tracks, and electromagnetic and hadronic cascades. By combining these results limits on the best possible reconstruction accuracy in energy and direction for the initial neutrinos achievable with an ORCA-type detector are derived.